Manajemen Pelayanan Pemberdayaan Anak Yatim pada Lembaga Amil Zakat Yatim Mandiri di Surabaya - Ana Toni Roby Candra Yudha (Al Tijarah, 2016)
The background this study are: firstly, there are a number of zakat institutions in Indonesia, both agencies and institutions amil amil zakat zakat is still not able to optimally collect zakat funds, infaq, and sadaqah of society. Second, the persistence of people's distrust of institutions in channeling zakat zakat funds, infaq, and sadaqah, so people still rely on the old way is by direct distribution. The third officer attitudes zakat institutions in serving mustahiq should be improved because it is related to the satisfaction and familial ties between the parties with mustahiq amil zakat institutions. The results of this study are as follows: First, empowerment conducted by Yatim Mandiri covers many aspects, such as economy, education, health services, humanitarian and others. Second, each of these aspects before, have the derivation in the form of empowerment programs. Third, Yatim Mandiri as amil zakat institutions that focus on empowering orphans/dhuafa was also to empower the poor, Fourth, Yatim Mandiri as amil zakat institutions have a number of donations and charity infaq much larger than the amount of zakat donations, with ratio of 80:20, and Fifth, the service provided by the Yatim Mandiri to the poor and needy got a very good assessment from the their mustahiq. Overall, the conclusion from this study is tha t the Yatim Mandiri has done his duty to the optimum as evidenced by the very positive assessment of mustahiq and empowering the poor to the services them, and they provide from time to the time.